Evaluasi Program Pembinaan Kompetensi Guru Pendidikan Agama Katolik di Bimas Katolik Kantor Wilayah Kementerian Agama Provinsi Bali - Utomo, A.N.; Yudana, I.M.; Divayana, D.G.H. (Jurnal Administrasi Pendidikan Indonesia, 2023)
This study aims to describe the effectiveness of the implementation of the Catholic Religious Education Teacher Competency Development program at the Catholic Community Guidance Office of the Ministry of Religion of Bali Province in terms of context, input, process, and product variables. Then evaluate together in terms of context, input, process, and product, as well as the constraints encountered and the solutions. The subjects in this study were 60 Catholic Religious Education Teachers who had participated in Catholic Religious Education Teacher Competency Development at the Catholic Community Guidance Center who were selected based on census techniques. This research is an evaluation research with a quantitative approach using the CIPP model (context, input, process, and product). Data were collected by means of questionnaires, documentation, and interviews and were analyzed descriptively quantitatively. Data analysis was performed by converting the raw score into a Z score (z-score) followed by a T score and then converted into the Glickman quadrant. The results of the study show the effectiveness of the implementation of the Catholic Religious Education Teacher Competency development program in Catholic Community Guidance in terms of the context obtained effective results (+), the effectiveness of the implementation of the Catholic Religious Education Teacher Competency development program in Catholic Community Guidance in terms of input obtained effective results (+), the effectiveness of program implementation Catholic Religious Education Teacher Competency Development in Catholic Community Guidance in terms of the process obtained effective results (+), the effectiveness of the implementation of the Catholic Religious Education Teacher Competency Development program in Catholic Community Guidance in terms of the product obtained effective results(+). Overall, the evaluation of context, input, process, and product variables in the implementation of the Catholic Religious Education Teacher Competency development program at the Catholic Community Guidance is classified as very effective (+ + + +).